Pepsin-Assisted Synthesis of Nano-Spinel (CoAl2O4) for Photodegradation of Congo Red, Methylene Blue and Methyl Orange - Gul, Enis Muhammet; Dumanli, Fatma Tugce Senberber; Derun, Emek Moroydor (SPRINGER INT PUBL AG, 2026)
The spinel-type of blue-coloured cobalt aluminate (CoAl2O4) was synthesized with a cubic lattice structure, exhibiting enhanced photocatalytic properties by using a pepsin-assisted co-precipitation procedure. The optimum sample prepared at 1200 degrees C and 3 h, following an ultrasound treatment with pepsin enzyme, exhibited nanoparticle formation in the 25-40 nm range. The highest removal percentages were found as 87.41% for Congo Red (CR), 74.49% for Methylene Blue (MB), and 68.35% for Methyl Orange (MO). The photodegradation kinetics were found to be best described by the first-order Langmuir-Hinshelwood model. The photocatalytic half-life (t(0.5)) values were found as 63.59, 192.54 and 216.61 min for the CR, MB and MO, respectively. Comprehensive radical trapping experiments and mechanism analysis revealed that while photogenerated holes (h(+)) are the primary reactive species for CR, hydroxyl radicals (.OH) play a dominant role in the degradation of the cationic MB dye. FT-IR analysis of the recycled catalyst confirmed the structural integrity and stability of the CoAl(2)O(4)nano-spinels after three cycles. These findings suggest that pepsin-assisted CoAl(2)O(4)is a robust and versatile photocatalyst for the effective degradation of diverse organic pollutants in wastewater treatment.
Keywords: CoAl2O4; Kinetic; Pepsin; Photodegradation; Spinel; COBALT ALUMINATE NANOPARTICLES; GREEN SYNTHESIS; PIGMENT; COMBUSTION; PHOTOCATALYST; REMOVAL; DYE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources